Analisis Ketebalan Potensi Bahan Galian dengan Menggunakan Metode Geolistrik di Kelurahan Togafo, Kota Ternate - Syarifullah Bundang; Said Hi Abbas; Minarti (JFT : Jurnal Fisika dan Terapannya, 2023)
The volcanic activity of Mount Gamalama in Ternate City greatly affects the geological conditions, especially the rock types in Togafo Village. There are outcrops of economically valuable minerals such as volcanic breccia deposits with a thickness of up to 5.8 m, but the vertical continuity of this layer is still unknown, so further research is needed. Geoelectric methods can be used to determine subsurface geological conditions. This research aims to analyze the thickness of potential volcanic breccia excavation material in Togafo Village, Ternate City. Some of the data used such as sounding geoelectrical measurements for 2 tracks using Schlumberger configuration, drilling using hand auger, and megascopic description of rock outcrops. The results show there are 2 layers in the subsurface, where the geoelectrical data shows that layer 1 is interpreted as a layer of sandy silt rock with a thickness of 0.6895 m at a depth of 0 - 0.6895 m with a resistivity value between 8.11 - 18.3 Ωm, and layer 2 is interpreted as a layer of volcanic breccia rock at a depth of 0.6895 - 25.4 m with a thickness of 24.7105 m with a resistivity value of 80 - 302 Ωm. This is also in accordance with the results of shallow drilling which shows the thickness of the top soil in the form of sandy silt is 0.45 m. So, it can be concluded that the average thickness of potential excavation material in the form of volcanic breccia rock layers is 24.7105 m.